Lethe gregoryi Watkins (Lepidoptera, Nymphalidae, Satyrinae), a distinct species - Lang, Song-Yun (Zootaxa, 2015)
In this paper, Lethe helle gregoryi Watkins, 1927 is raised to specific status, viz. L. gregoryi stat. nov., and L. moelleri bitaensis Yoshino, 1999 syn. nov. is found to be a junior synonym of gregoryi. Lethe gesangdawai Huang, 2001 is sunk to a subspecies of L. gregoryi, viz. L. gregoryi gesangdawai stat. nov.